HUBUNGAN POLA ASUH ORANGTUA DENGAN HASIL BELAJAR SISWA DAN IMPLIKINYA TERHADAP PELAYANAN BIMBINGAN DAN KONSELING - Emi Karnangsyah (Indonesian Institute for Counseling, Education and Therapy (IICET), 2017)
The purpose of this research is to know the result of learning the student, the pattern to take care of the parent, and relation between the pattern of taking care of the parent with result of learning the student its implication to guidance and counseling in SMP Negeri 36 Sarolangun. The research is conducted with correlation descriptive method, that is one research to look for relation between on variable with other variable and then the data or information is elaborated by using approach of quantitative, that is correlating between the pattern take care of parent and result the learning the student. The Result of this research that are: (1) the result of learning SMP Negeri 36 Sarolangun on the part of is, (2) The pattern take care of SMP Negeri 36 Sarolangun as following: The authoritative parenting reside in high categories, the uninvolved reside high categories. The based on this research that researcher have found. This can be know that the relation which between the pattern take care with result of learning the student.